MODERASI CORPORATE GOVERNANCE PADA HUBUNGAN EARNINGS MANAGEMENT DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) (Pada Perusahaan Yang Listing Di Bursa Efek Indonesia Peserta Corporate Governance Perception Index Tahun 2010-2014) - Yuliana, Yuliana (Katalogis, 2016)
The Study determine the moderation of corporate governance on the relationship between earning management and corporate social responsibility disclosure of the companies listed on Indonesia stock exchange as participants of corporate governance perception index in 2010-2014. Population of this study consist of 35 companies listed on Indonesia stock exchange as participants of corporate governance perception index in 2010-2014. Sampling technique used is purposive sampling, by wich this study selected 6 companies as samples. Technique analysis is data panel regressions with Moderate Regression Analysis (MRA) method; hypothesis testing is using t-statistics to determine the partial regression coefficient with significant level of 5%. The study has resulted two empirical finding. Fisrt, earning management has positive but insignificant influence on corporate social responsibility disclosure. Second, variabel of corporate governance that proxied with corporate governance perception index score is unable to moderate the relationship between earning management and corporate social responsibility disclosure.